2008
DOI: 10.1002/ejsp.577
|View full text |Cite
|
Sign up to set email alerts
|

Generality and specificity in stereotypes of out‐group power and benevolence: Views of Chechens and Jews in the Russian federation

Abstract: We examined the ascription of five characteristics (moral, peaceful, antagonistic, smart, show initiative) to Chechens and Jews in a large, diverse, sample of participants in the Russian Federation. Factor analysis showed these five characteristics to fit within the expected two-dimensional structure of power (smart, show initiative) and benevolence (moral, peaceful, antagonistic). Consistent with historical stereotypes, Factor analysis showed power to be the more empirically important dimension regarding Jews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…Fiske, Cuddy, and their colleagues have suggested in a number of recent papers (Caprariello, Cuddy, & Fiske, 2009; Cuddy, Fiske, & Glick, 2007, 2008; Fiske, Cuddy, & Glick, 2007; Fiske, Xu, & Cuddy, 1999; Fiske et al., 2002) that the content of outgroup stereotypes around the world can be predicted from outgroups’ sociostructural position, namely their relative status and the degree to which they are seen as competing with the ingroup. In both Western and non‐Western samples, higher‐status groups are stereotyped as more competent than lower‐status groups, and more competitive, threatening groups are stereotyped as less warm (Cuddy et al., 2009; Eckes, 2002; Fiske et al., 2002; Leach et al., 2008). In complementary thinking on gender stereotypes, Eagly and colleagues have demonstrated that stereotypes of men as agentic and women as communal arise from the social roles they play as breadwinners and caregivers, respectively (Cejka & Eagly, 1999; Eagly, 1987; Eagly & Steffen, 1984, 1986; Eagly, Wood, & Diekman, 2000).…”
Section: Stereotype Stabilitymentioning
confidence: 99%
“…Fiske, Cuddy, and their colleagues have suggested in a number of recent papers (Caprariello, Cuddy, & Fiske, 2009; Cuddy, Fiske, & Glick, 2007, 2008; Fiske, Cuddy, & Glick, 2007; Fiske, Xu, & Cuddy, 1999; Fiske et al., 2002) that the content of outgroup stereotypes around the world can be predicted from outgroups’ sociostructural position, namely their relative status and the degree to which they are seen as competing with the ingroup. In both Western and non‐Western samples, higher‐status groups are stereotyped as more competent than lower‐status groups, and more competitive, threatening groups are stereotyped as less warm (Cuddy et al., 2009; Eckes, 2002; Fiske et al., 2002; Leach et al., 2008). In complementary thinking on gender stereotypes, Eagly and colleagues have demonstrated that stereotypes of men as agentic and women as communal arise from the social roles they play as breadwinners and caregivers, respectively (Cejka & Eagly, 1999; Eagly, 1987; Eagly & Steffen, 1984, 1986; Eagly, Wood, & Diekman, 2000).…”
Section: Stereotype Stabilitymentioning
confidence: 99%
“…Uma primeira selecção das características foi efectuada a partir da recolha de características presentes nos estudos descritos na secção de revisão da literatura (Costa & McCrae, 1995;Graham, Haidt, & Nosek, 2008;Haidt & Graham, 2007;Kohlberg, 1992;Leach, Ellemers & Barreto, 2007;Leach, Minescu, Poppe, & Hagendoorn, 2008;Phalet & Poppe, 1997;Schwartz, 1992).…”
Section: Methodsunclassified
“…Assim, alguns autores têm procurado clarificar o papel da moralidade, a par com as outras dimensões fundamentais de percepção (Kay & Jost, 2003;Leach, Minescu, Poppe, & Hagendoorn, 2008;Phalet & Poppe, 1997;Wojciszke, 1994Wojciszke, , 2005, baseando-se, na sua maioria, em abordagens atribuicionais e/ou associativas de traços de moralidade a determinados alvos, grupais ou individuais.…”
unclassified
“…Methods based in interpersonal perception and group stereotypes provide a new way of empirically studying national images. There has been considerable research in the domain of intergroup perception analyzing how people judge members from other groups in stereotypic ways (e.g., Eagly & Kite, 1987; Katz & Braly, 1933; Leach, Minescu, Poppe, & Hagendoorn, 2008; Madon et al., 2001; Vinacke, 1949). Such research shows evidence of two important general findings (see Schneider [2004] for a review).…”
Section: Intergroup Perception and Projectionmentioning
confidence: 99%
“…Such research shows evidence of two important general findings (see Schneider [2004] for a review). First, people often assume that groups to which they belong and higher status groups are more positively evaluated than groups to which they do not belong or which have low social status (e.g., Leach et al., 2008). Second, people are often implicitly in‐group‐centric, judging other groups by the standards of their own group (e.g., Hegarty & Pratto, 2001).…”
Section: Intergroup Perception and Projectionmentioning
confidence: 99%